2010
DOI: 10.1177/1087054709356388
|View full text |Cite
|
Sign up to set email alerts
|

A Compound Herbal Preparation (CHP) in the Treatment of Children With ADHD: A Randomized Controlled Trial

Abstract: The well-tolerated CHP demonstrated improved attention, cognition, and impulse control in the intervention group, indicating promise for ADHD treatment in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Alternative, safe, and well-tolerated ADHD interventions that demonstrate efficacy in improving ADHD symptoms can potentially broaden the scope of therapeutic options available to children, and as such warrant further study and consideration (Katz et al, 2010), If dietary interventions (restricted diets and/or nutritional supplementation) were found to be consistently beneficial in a substantial number of children with ADHD, then treatment guidelines would require revision (Nigg et al,, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative, safe, and well-tolerated ADHD interventions that demonstrate efficacy in improving ADHD symptoms can potentially broaden the scope of therapeutic options available to children, and as such warrant further study and consideration (Katz et al, 2010), If dietary interventions (restricted diets and/or nutritional supplementation) were found to be consistently beneficial in a substantial number of children with ADHD, then treatment guidelines would require revision (Nigg et al,, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…In a review conducted by Chan (2002) megadose-vitamin therapies and mineral supplements such as iron, pyridoxine, zinc, magnesium, and coenzyme Q, along with other supplements, have been used in an attempt to treat ADHD symptomatology. Katz, Levine, Kol-Degani, and Kav-Venaki (2010) conducted a randomized, doubleblind, placebo-controlled trial to evaluate the efficacy of a patented compound herbal preparation (CHP) in improving attention, cognition, and impulse control in children with ADHD. The treatment group showed statistically significant results when compared to the placebo group.…”
Section: Biochemical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an open 4-week trial, 74% of children and adolescents with ADHD who were prescribed a combination of ginseng extract and G. biloba were rated as improved by their parents [66]. Finally, after a 4-month trial of a compound herbal preparation compared with placebo, children assigned to the compound herbal preparation improved significantly on a computerized measure of attention and impulsivity; however, no parent or teacher ratings were reported [67]. Given these noncompelling results and possible risks, herbal treatments will require additional evidence before they can be recommended for treatment of ADHD.…”
Section: Note Regarding Herbal and Homeopathic Treatmentsmentioning
confidence: 99%
“…A meta-analysis of 6 studies found that there is a modest increase in oxidative stress in ADHD children and adults [12]. In addition, several studies had found that with anti-oxidant usage, children with ADHD had better behaviour scores [13][14][15]. TRF may also work by inhibiting glutamate-induced activation of phospholipase A2 (PLA2) in brain tissue, resulting in better metabolism of polyunsaturated fatty acids (PUFAs) [16].…”
Section: Introductionmentioning
confidence: 99%